Information and Knowledge Processes in Health Care Value Co-Creation and Co-Destruction - Valtteri Kaartemo; Helena Känsäkoski (Sage, 2022)
The purpose of this article is to explore how information and knowledge processes (IKPs) influence co-creation and co-destruction of value in a health service system. A qualitative, single embedded case-approach is taken to develop theory through a systematic combining of theoretical framework, empirical fieldwork, and case analysis. Six theoretical propositions are set to describe the linkage between IKPs and value co-creation (and co-destruction). The article contributes to health marketing and transformative service research by linking organizational activities to the motivation and empowerment of patients and their families, by highlighting the importance of the role of knowledge integration in value co-creation, by introducing a shift toward systems thinking, by conceptualizing value as manifested as health behavior change, and by underlining that health care processes may have a negative (value co-destructing) influence on the well-being of actors.